Model Penguatan Pesan Damai Ala Wahid Foundation bagi Pendidikan Karakter Pemuda Muslim Jakarta Pusat - Usman Sutisna (Universitas Indraprasta PGRI Jakarta, 2021)
This study aims to analyze the peace concept of the Wahid Foundation and to analyze the application of the peace concept of K. H. Abdurrahman Wahid for youth. This research uses Ursula Martius Franklin's theory and binary logic law theory about peace. The method used is a qualitative research method with data collection through field observations, documentation, literature study, and interviews. The results obtained from this study were the Wahid Foundation peace concept, namely tolerance and respect for differences. Tolerance is characterized by accepting the existence of people or followers of different religions accompanied by respect for fellow human beings, the manifestation of this tolerance is an attitude of respect for plurality, respect for opinions. , an attitude of openness to differences, helping and defending as well as respecting people who are oppressed or treated unfairly, and upholding human brotherhood. Youth can also use some of the Wahid Foundation models in implementing this concept in the school environment through the peaceful school program, namely by means of dialogue, discussion, and simulation. Thus youth are trained to think critically, openly, and creatively and be able to position themselves when faced with situations that require tolerance to be applied.